A Mechanical Stimulation Glove to Induce Hebbian Plasticity at the Fingertip - Timm, Fabian; Kuehn, Esther (Frontiers in Human Neuroscience, 2020)
Repetitive sensory stimulation of the fingertip induces Hebbian plasticity in the sensorimotor cortex that benefits tactile and motor behavior of the hand in healthy younger adults, older adults, and patients. To use this method outside the laboratory, robust and portable stimulation systems are needed that allow prolonged stimulation phases over several hours without compromising on signal intensity or personal mobility. Here, we introduce two stimulation gloves that apply finger- and frequency-specific mechanical stimulation to individual fingertips over prolonged time periods. The stimulators are built into commercially available cotton gloves and apply stimulation either via loudspeaker membranes, or via linear resonant actuators. We tested the efficiency of both gloves to induce Hebbian plasticity in younger adults by using two established measures of tactile performance, the grating orientation task (GOT) and the two-point discrimination task (2PDT). Both tests were performed before and after three hours of sensory finger stimulation using one of either glove system. As a control condition, a non-stimulated finger was tested in both tasks before and after stimulation. The results show no significant effect of sensory stimulation on GOT thresholds, but a significant decrease in the 2PDT thresholds after compared to before the training at the stimulated finger only. The loudspeaker membrane improved performance in the 2PDT in 10/16 participants, whereas the linear resonant actuator improved performance in the 2PDT in 13/16 participants. Stimulation gloves with built-in modules may be used in future larger scale cohort studies on sensorimotor plasticity, rehabilitation, and learning.